Prevalence and correlates of childhood anemia in the MINA-Brazil birth cohort study - Cardoso, Marly A.; Lourenço, Bárbara H.; Matijasevich, Alicia; Castro, Marcia C.; Ferreira, Marcelo U. (Revista de Saúde Pública, 2023)
OBJECTIVE: To describe the prevalence and predictors of childhood anemia in an Amazonian population-based birth cohort study. METHODS: We estimated the prevalence of maternal anemia at delivery (hemoglobin [Hb] concentration < 110 g/L) in women participating in the MINA-Brazil birth cohort study and in their children examined at 1 and 2 years (Hb < 110 g/L) and at 5 years of age (Hb < 115 g/L). We measured ferritin, soluble transferrin receptor, and C-reactive protein concentrations in mothers at delivery and in their 1- and 2-year old children to estimate the prevalence of iron deficiency and its contribution to anemia, while adjusting for potential confounders by multiple Poisson regression analysis (adjusted relative risk [RRa]). RESULTS: The prevalence 95% confidence interval (CI) of maternal anemia, iron deficiency, and iron-deficiency anemia at delivery were 17.3% (14.0–21.0%), 42.6% (38.0–47.2%), and 8.7% (6.3–11.6)%, respectively (n = 462). At age 1 year (n = 646), 42.2% (38.7–45.8%) of the study children were anemic, 38.4% (34.6–42.3%) were iron-deficient, and 26.3 (23.0–29.9) had iron-deficiency anemia. Prevalence had decreased to 12.8% (10.6–15.2%), 18.1% (15.5–21.1%), and 4.1% (2.8–5.7%), respectively, at 2 years (n = 761); at 5 years of age, 5.2% (3.6–7.2%) children were anemic (n = 655). Iron deficiency (RRa = 2.19; 95%CI: 1.84–2.60) and consumption of ultraprocessed foods (UPF) (RRa = 1.56; 95%CI: 1.14–2.13) were significant contributors to anemia at 1 year, after adjusting for maternal schooling. At 2 years, anemia was significantly associated with maternal anemia at delivery (RRa: 1.67; 95%CI: 1.17–2.39), malaria since birth (2.25; 1.30–3.87), and iron deficiency (2.15; 1.47–3.15), after adjusting for child ’s age and household’s wealth index. CONCLUSIONS: Anemia continues to be highly prevalent during pregnancy and early childhood in the Amazon. Public health policies should address iron deficiency, UPF intake, maternal anemia, and malaria in order to prevent and treat anemia in Amazonian children.